Diphosphorus Tetraiodide (P2I4): An Efficient Catalyst for Synthesis of 2-Aryl-1,3-benzazoles via Cyclocondensation of o-Amino/Mercaptan/Hydroxy Anilines with Aryl Acids - Bhagat, Saket B.; Sutar, Yogesh B.; Manohar, Yogesh; Telvekar, Vikas N. (Asian Journal of Chemistry, 2017)
An efficient and versatile approach for the synthesis of 2-substituted 1,3-benzazoles has been developed via diphosphorus tetraiodide (P2I4) catalyzed condensation reaction of ortho-substituted anilines (–NH2, –SH and –OH) with various aromatic acids to give benzimidazoles, benzothiazoles and benzoxazoles in excellent yields. Additionally, the synthetic approach reported herein has advantages such as mild reaction conditions, broad substrate scopes as well as simple one-pot operation, common for all the three 1,3-benzazoles, which makes this strategy highly attractive.